Targeting m6A RNA Modification in Tumor Therapeutics - Zhenwei Mao; Min Li; Shengjun Wang (Current Oncology)
The prevalent eukaryotic RNA modification N6-methyladenosine (m6A), which is distributed in more than 50% of cases, has demonstrated significant implications in both normal development and disease progression, particularly in the context of cancer. This review aims to discuss the potential efficacy of targeting tumor cells through modulation of m6A RNA levels. Specifically, we discuss how the upregulation or downregulation of integral or specific targets is effective in treating different tumor types and patients. Additionally, we will cover the factors influencing the efficacy of m6A RNA targeting in tumor treatment. Our review will focus on the impact of targeting m6A mRNA on genes and cells and assess its potential as a therapeutic strategy for tumors. Despite the challenges involved, further research on m6A RNA in tumors and its integration with existing tumor therapy approaches is warranted.